Somatic and germline aberrations in homologous recombination repair genes in Chinese prostate cancer patients - Liu, Yixiao; Jin, Bo; Shen, Cheng; Gao, Xianshu; Qi, Xin; Ma, Mingwei; Li, Hongzhen; Hao, Han; Tang, Qi; Yang, Kaiwei; Mi, Yue; Guan, Jie; et al. (Frontiers in Oncology, 2023)
BACKGROUND: Homologous recombination repair deficiency is associated with higher risk and poorer prognosis for prostate cancer. However, the landscapes of somatic and germline mutations in these genes remain poorly defined in Chinese patients, especially for those with localized disease and those from north part of China. In this study, we explore the genomic profiles of these patients. METHODS: we performed next-generation sequencing with 200 tumor tissues and 714 blood samples from prostate cancer patients at Peking University First Hospital, using a 32 gene panel including 19 homologous recombination repair genes. RESULTS: In total, 2.5% (5/200) patients harbored somatic aberrations in homologous recombination repair genes, and 4.1% (29/714) patients harbored germline aberrations. TP53, PTEN, ATM were the most common somatic aberrations; ATM, BRCA2, NBN were the most common germline aberrations. 196 (98.0%) somatic-tested and 519 (72.7%) germline tested patients underwent prostatectomy, of which 28.6% and 42.0% had Gleason scores ≥8 respectively. Gleason score at either biopsy or prostatectomy and risk group were both predictive for somatic aberrations in general and in TP53, while age of onset <60 years old was the only clinical factor associated with positive germline aberrations in BRCA2/ATM. CONCLUSIONS: Our results showed a distinct genomic profile in homologous recombination repair genes for patients with prostate cancer across all clinical states from north China. Clinicians may consider to expand the prostate cancer patients receiving genetic tests to include more individuals due to the weak guiding role by the clinical factors currently available.